Nowe metody obliczania średnich ruchomych i ich zastosowanie w analizie technicznej - Borowski, Krzysztof (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
One of the basic assumption of technical analysis is that stock move in trends. Since major trends comprise many minor fluctuations in prices, an MA is constructed to help smooth out the data so the underlying trend will be more clearly visible. Three basic types of MAs have been used in for more than 40 years the technical analysis of stock trends: simple, weighted, and exponential. There is no such thing as a perfect average. Development of computing techniques has brought new ideas and concepts to practicable applications of the moving averages. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 42-54